International Students’ Accommodation and Politeness Strategies for Dealing with Communication Conflicts: A Case Study at a State University in Surabaya - Sari, Yanuarita Kusuma Permata; Widita, Anindya; Zunaidah, Asih (UI Scholars Hub, 2019)
There must be quite a number of international students leaving their homelands and living in a foreign country to study. This case study is expected to provide useful insights into social adaptation strategies used by international students. The theory used in the framework is the Communication Adaptation Theory (CAT) and Politeness Strategies Theory. This research is a case study, in which a descriptive-qualitative approach was employed, it was conducted in UNAIR (University of Airlangga), Surabaya. The data were collected through interviews and observation. The informants were selected by using the purposive technique. The results revealed that most of the students applied the negative politeness strategy, which went in line with the divergence strategy in accommodation theory, as they tried to maintain their identity in a foreign place.